1981
DOI: 10.17848/9780880995610
|View full text |Cite
|
Sign up to set email alerts
|

A Fisherman's Guide: An Assessment of Training and Remediation Strategies

Abstract: The W.E. Upjohn Institute is pleased to publish a comprehensive review of training and remediation strategies for unemployed and underemployed persons. Although employability development programs that emphasize relatively longterm investments in training have been subordinate to programs that provide jobs, this orientation was largely due to the short-term goals inherent in both the policy orientation and management of the Comprehensive Employment and Training Act.The author clearly notes the need to reorient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The problem of access for disadvantaged youth has been most often addressed by special programs emphasizing job preparation, job seeking skills, and work orientation training, as well as job development and "supported work initiatives (Levin & Ferman, 1985;Michel, 1980;Taggart, 1981). Even more promising, however, have been programmatic efforts to address the problem of negative characteristics in existing youth jobs Downloaded by [New York University] at 04:36 14 May 2015 by "designing" structured paid work experiences for youth.…”
Section: Journal Of Crime and Justice 33mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of access for disadvantaged youth has been most often addressed by special programs emphasizing job preparation, job seeking skills, and work orientation training, as well as job development and "supported work initiatives (Levin & Ferman, 1985;Michel, 1980;Taggart, 1981). Even more promising, however, have been programmatic efforts to address the problem of negative characteristics in existing youth jobs Downloaded by [New York University] at 04:36 14 May 2015 by "designing" structured paid work experiences for youth.…”
Section: Journal Of Crime and Justice 33mentioning
confidence: 99%
“…Unfortunately, assumptions about general incompetence of young offenders in many of these efforts have often led to an over-emphasis on molding the work to fit the needs of the worker--resulting in inadequate attention to the value and quality of the work itself. Charges of "make work have been a frequent, though predictable, outcome (Taggart, 1981).…”
Section: Public and Participant Value Of Offender Workmentioning
confidence: 99%
“…For a summary of these studies, see Taggart, 1981;Barnow, 1986;Danziger and Weinberg, 1986, pp. 133-179. In 1988 Congress enacted the Worker Adjustment and Retraining Notification Act, which requires that employers with 100 or more employees must provide advance notice 60 days prior to a plant closing or relocation.…”
Section: Endnotesmentioning
confidence: 99%
“…Many studies have been conducted to evaluate the impact of earlier job training programs on the economically disadvantaged.2 The consensus among these studies is that job training programs have been successful in raising participants' postprogram earnings and their employment probability (Long, Mallar, and Thornton, 1981;Taggart, 1981). Among such programs, classroom skill training, classroom basic training, and OJT have been especially beneficial for participants.…”
mentioning
confidence: 99%
“…Those programs were controversial, however. Supporters believed that thousands of people who had not received adequate education and training in the public schools were helped (Taggart, 1981). Opponents suggested that jobs were created in the bureaucratic administration of the programs, but that minorities and other groups needing help were not aided in proportion to dollars spent (Brophy, 1979;Cameron, 1979).…”
Section: Description Of the Problemsmentioning
confidence: 99%